Detection and Neutralization Tax Offenses Operational Employees of Law Enforcement Bodies - V. V. Firsov (Евразийская интеграция: экономика, право, политика, 2019)
The article deals with the specifics of identifying and neutralizing the facts of tax offenses, which requires special attention from the side of tax and law enforcement agencies and is one of the important policies of each state that respects the rights and freedoms of citizens and protects these rights by legal means.